Sistem Skoring Nefrometri R.E.N.A.L: Sistem Berstandar yang Komprehensif Dalam Menilai Ukuran, Lokasi, dan Kedalaman Tumor Ginjal - REZA, MOCHAMMAD; RAKHMAN, ARIEF; MOCHTAR, CHAIDIR A (Indonesian Journal of Cancer, 2014)
The treatment of localized renal cell carcinoma remains subjective.The R.E.N.A.L.- Nephrometry Score quantifies the characteristics of renal mass anatomy based on radiologic findings to provide a standardized objective descriptive system in an reproducible manner. We evaluate the utility of this system in predicting tumor resectability, operative approach and risk of complication, and their relevance to clinical practice.Electronic literature research was performed to access the main series of literature in the past 4 years since the scoring system developed. The articles were then analyzed and selected to address these issues. Fifteen peer-reviewed publications (2009 to 2012) were selected. Most of the studies were analyzed using the prospective acquired database. Increasing tumor complexity was asscociated with greater overall nephrometry score in patient underwent renal neprectomy and partial neprectomy. Compared with patients who underwent partial nephrectomy, the patients treated with radical nephrectomy had a significantly greater size (R), central proximity (N), and location (L) component scores. There were more complications among patients with higher R.E.N.A.L scores who underwent partial nechrectomy (PN) thanin patients with PN who did not developcomplications. The R.E.N.A.L nephrometry scoring system has good interobserver reliability showed by the similar sum of nephrometry score concordance to the R, E, N, A, and L components among surgeons in different centre. The R.E.N.A.L nephrometry standardize the reporting of solid renal masses and appears to effectively stratify the treatment choice for patients. Nephrometry aids in objectifying previously subjective measure and provide more meaningful comparison of treatment recommendation or results in published series.